Additive electrospraying for scaffold functionalization - Abdul Khodir, Wan Khartini; Altobelli, Rosaria; Guarino, Vincenzo; Ambrosio, Luigi (Elsevier Inc., 2018)
In the last decade, micro- and nanostructured platforms with interesting features as bioactive carriers have been fabricated by the deposition of electrospun fibers exhibiting extended surface area and high molecular permeability associated with fully interconnected pore architecture, thus creating the opportunity to incorporate a wide range of actives/drugs for different use. In these systems, molecular release may occur via various molecular transport pathways, namely diffusion, desorption, and scaffold degradation, which may be tuned through a careful control of fiber morphology and composition. Recent studies have demonstrated that several shortcomings involve the possibility to incorporate bioactive species, not exposing molecules to fast and/or uncontrolled denaturation, thus preserving biochemical and biological fiber functionalities.